HUBUNGAN ANTARA PAPARAN IKLAN PANGAN DI TELEVISI DENGAN KONSUMSI SNACK DAN FAST FOOD PADA REMAJA SMP DI YOGYAKARTA - , EMILIA CHOIRIAH, Muhammad Dawam Jamil, SKM, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: There are many food advertisings in television. Adolescent is one of the targets of those advertisings. The advertisings are packaged in such a way to attract the adolescent. The more food advertising, the more food choice that can be consumed. The more snack and fast food are consumed, the greater likelihood of health problems that will be affected to adolescent. Objective: To examine the association among food advertising exposure, student allowance, television viewing, and household income with snack and fast food consumption towards secondary school adolescents in Yogyakarta. Method: This is an observational study with cross-sectional method. Sampling was using proportional stratified random sampling. The subject are 7 th , 8 th , and 9 th grade students of SMP N 1, SMP N 2, and SMP N 4 Yogyakarta. Data collection was using questionnaire that contains questions about food advertising in television. Body weight and body height were assessed to discover the nutritional status. Data analysis was using chi-square method. Result: P value 0,00 (p < 0,05) for the association between food advertising exposure with snack and fast food consumption. P value 0,037 (p < 0,05) for the association between student allowance with snack and fast food consumption. P value 0,001 (p < 0,05) and p value 0,014 (p < 0,05) for the association among television viewing during weekdays and weekends with snack and fast food consumption. P value 0,832 (p > 0,05) for the association between household income with snack and fast food consumption. Conclusion: Food advertising exposure is associated with snack and fast food consumption towards secondary school adolescents. Student allowance is associated with snack and fast food consumption towards secondary school adolescents. Television viewing is associated with snack and fast food consumption towards secondary school adolescents. Household income is not associated with snack and fast food consumption towards secondary school adolescents.